Qualifications of Cooperative Education Students that Establishments in the Lat Krabang Industrial Estate Require According to the Thai Higher Education Qualifications Framework - พรหมทอง ปิยาภา; กลั่นมา อาจารย์กวีกานต์; โตสัจจะวงษ์ อาจารย์จรูญวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study the characteristics of cooperative education students that the establishments in Ladkrabang Industrial Estate required according to the Thai Qualification Framework (TQF) in 4 aspects: 1. Knowledge 2. Skills 3. Ethics 4. Personal characteristics. A survey study was used to collect data using a questionnaire. The population used in the research was the HR heads of 23 establishments in the Lat Krabang Industrial Estate where students of Bangkok Suvarnabhumi University participated in their internship. The sample was selected using the purposive sampling method. Data were analyzed by finding the mean and standard deviation (SD.) The results of the study showed that the qualifications of cooperative education students required by establishments in the Ladkrabang Industrial Estate Zone were in accordance with the framework of Thai higher education qualification standards in all four aspects. The highest average value was , followed by personality ( = 4.71, SD=0.66), skills( = 4.11, SD=0.48), and knowledge ( = 4.03, SD=0.64), respectively.